L’atelier institué en portrait de l’artiste moderne dans la littérature du XIXe siècle - Rodriguez, Véronique (RACAR : Revue d'art canadienne / Canadian Art Review)

(untitled) (UAAC-AAUC (University Art Association of Canada | Association d'art des universités du Canada), 1999)
This article analyses the importance of the artist’s studio in some nineteenth-century French novels. In these texts, the studio comprises many typical motifs, repeated from one novel to the next: the difficulty of its access, the particular quality of its lighting, and specific pieces of furniture – mirror, folding screen, stove and divan. Besides these descriptive aspects, the studio also contributes to secure the artist in his creative role. These invariables participate in the construction of the artist’s identity in setting out the different levels of his interactions – the relations to the self, to the other, and to the group – all of them subsumed in the sole motif of the stove, emblematic condenser of these multiple relationships. This analysis also reveals that, for these writers, the studio can also be instituted as the real portrait of the artist by evoking an aesthetic, as well as by staging the social conditions of its occupant. When the artist becomes an important protagonist in his “milieu,” the studio is not a mere “architectural container,” but the real psychological mirror of the hero. In order to explain the metonymic and metaphoric aspects of the studio, this study examines in more depth Jules and Edmond de Goncourt’s novel, Manette Salomon (1867), because of the particular status that the authors have given it.